2018
DOI: 10.1186/s40635-018-0205-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of particulate exposure during continuous drug infusion in critically ill adult patients: a preliminary proof-of-concept in vitro study

Abstract: BackgroundIn critically ill patients, drug incompatibilities frequently occur because of the number of drugs to be administered through a limited number of infusion lines. These are among the main causes of particulate contamination. However, little data is available to quantify particle exposure during simultaneous IV-drug infusion. The objective of this study was to evaluate the particulate matter potentially administered to critically ill patients.MethodsThe particulate matter (between 1 μm and 30 mm) of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…The particulate contaminants can be detectable particles that are visible on visual inspection with sizes ≥50 µm or sub-visible particles that are not detectable on visual inspection with sizes varying between 2 and 50 µm 36 . Both visible and sub-visible particulate contaminations in parenteral fluids or solutions are dangerous [36][37][38][39][40] as these fluids are meant to pass through the blood vessels. The present study showed that the drug products are free from both visible and sub-visible particulate contaminations and their use cannot lead to the deleterious effects of particulate contamination.…”
Section: Discussionmentioning
confidence: 99%
“…The particulate contaminants can be detectable particles that are visible on visual inspection with sizes ≥50 µm or sub-visible particles that are not detectable on visual inspection with sizes varying between 2 and 50 µm 36 . Both visible and sub-visible particulate contaminations in parenteral fluids or solutions are dangerous [36][37][38][39][40] as these fluids are meant to pass through the blood vessels. The present study showed that the drug products are free from both visible and sub-visible particulate contaminations and their use cannot lead to the deleterious effects of particulate contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, no standard recommendations have been issued by the three main Pharmacopoeias (European, American and Japanese) for dynamic particle counting. This work has been carried out in our laboratory using a new technique for the dynamic counting of non-visible particles (<50 µm) which indicates the potential particulate load to which patients are exposed [ 16 , 17 , 22 , 32 , 33 , 34 ]. With the use of this appliance, different assembly lines used for infusion protocols in intensive care units (adult, paediatric and neonatal) can be reproduced and studied in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the increasing complexity of intravenous therapy has brought renewed scrutiny to the presence of particulate matter in parenteral fluids. A number of in vitro studies have simulated multidrug protocols for neonatal, pediatric, and adult patients, many involving drug administration in conjunction with PN admixtures 47,48,52,60,67–70 . Variation exists in the lower range of particle sizes evaluated in these studies, which may reduce the ability to accurately determine the total number of particles in a given solution.…”
Section: Size and Number Of Particles In Pn Admixturesmentioning
confidence: 99%
“…Given the high degree of patient‐specific customization required for each PN admixture, not all instances of incompatibility or admixture instability can be predicted 3,50 . Studies have documented sharp increases in particulate matter when medications are co‐infused with PN, underscoring the importance of using appropriate administration techniques, including filters, when infusing medications in conjunction with PN 52,67,70 . Strategies that limit contact time between drugs, such as avoiding the use of extension sets, reduces particulate contamination during multidrug therapies 50,66,68 .…”
Section: Size and Number Of Particles In Pn Admixturesmentioning
confidence: 99%
See 1 more Smart Citation